2015
DOI: 10.1038/cddis.2014.554
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the translation initiation factor eIF2α at serine 51 determines the cell fate decisions of Akt in response to oxidative stress

Abstract: Phosphorylation of the α subunit of the translation initiation factor eIF2 at serine 51 (eIF2αP) is a master regulator of cell adaptation to various forms of stress with implications in antitumor treatments with chemotherapeutic drugs. Herein, we demonstrate that genetic loss of the eIF2α kinases PERK and GCN2 or impaired eIF2αP by genetic means renders immortalized mouse fibroblasts as well as human tumor cells increasingly susceptible to death by oxidative stress. We also show that eIF2αP facilitates Akt act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
89
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 70 publications
10
89
0
2
Order By: Relevance
“…9,32 Of particular interest, a report suggests that phosphorylation of eIF2a at serine 51 may control the activation of AKT promoting either cell death or survival in response to oxidative stress. 33 The latter studies are, therefore, compatible with our finding that the overexpression of CHIP inhibited the phosphorylation of eIF2a and of AKT. Altogether, the present data from both in vitro and in vivo models of global cerebral ischemia are consistent with the hypothesis that the overexpression of CHIP is sufficient to prevent neurodegeneration in the hippocampus.…”
Section: Discussionsupporting
confidence: 89%
“…9,32 Of particular interest, a report suggests that phosphorylation of eIF2a at serine 51 may control the activation of AKT promoting either cell death or survival in response to oxidative stress. 33 The latter studies are, therefore, compatible with our finding that the overexpression of CHIP inhibited the phosphorylation of eIF2a and of AKT. Altogether, the present data from both in vitro and in vivo models of global cerebral ischemia are consistent with the hypothesis that the overexpression of CHIP is sufficient to prevent neurodegeneration in the hippocampus.…”
Section: Discussionsupporting
confidence: 89%
“…Akt activation in MIN6 cells depleted of Nck1 may result from the inhibition of the mTORC1-dependent negative feedback loop leading to PI3K inhibition since mTORC1 activity was attenuated in these cells. Supporting this, a recent study illustrated an important role for PERK-dependent phosphorylation of eIF2αSer 51 in dictating cell death or survival to oxidative stress by activating Akt [67]. Indeed, it was demonstrated that peIF2αSer 51 has a prosurvival function against oxidative stress by downregulating mTORC1 activity, which then promotes Akt activation.…”
Section: Discussionmentioning
confidence: 86%
“…It can be inferred that phosphorylation of eIF2α is a master regulator of cell adaptation to ER stress conditions. It is also a significant checkpoint under which not only global protein translation, but also cell proliferation are blocked [68]. Furthermore, phosphorylated eIF2α has a negative influence on eIF2β functioning and acts as its major inhibitor [69].…”
Section: Activation Of the Perk/eif2a/atf4 Axis Of The Upr Under Smentioning
confidence: 99%